Unusual neurological presentation of Fusobacterium necrophorum disease. (12th January 2016) - Haddad, Nasrean; Morris, Trefor; Dhillon, Rishi; Gibbon, Frances
Abstract : A 2-year-old girl presented to hospital, with reduced consciousness and fever. She had a 4-week history of fever treated with two courses of amoxicillin for tonsillitis diagnosed in primary care. Neuroimaging revealed multiple cerebral abscesses and subdural empyema. Pus aspirated from the intracranial collections grew Fusobacterium necrophorum and meropenem was started. Following neurosurgery, the patient continued to be agitated with fluctuating fever. She underwent close monitoring with regular neuroimaging. To control the progression of intracranial infection, she underwent three separate neurosurgical procedures following which she made a good recovery. This case demonstrates how an organism rarely associated with childhood illnesses presented atypically and progressed into a complex potentially fatal intracranial infection requiring a high degree of neurosurgical intervention. Awareness of this organism is important. The combination of source control together with appropriate antibiotic use was crucial in controlling the infection.